2015
DOI: 10.1371/journal.pone.0134593
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and Molecular Characterization of Glucose-6-Phosphate Dehydrogenase Deficiency at the China-Myanmar Border

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is an X-linked hereditary disease that predisposes red blood cells to oxidative damage. G6PD deficiency is particularly prevalent in historically malaria-endemic areas. Use of primaquine for malaria treatment may result in severe hemolysis in G6PD deficient patients. In this study, we systematically evaluated the prevalence of G6PD deficiency in the Kachin (Jingpo) ethnic group along the China-Myanmar border and determined the underlying G6PD genotypes. We su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 37 publications
5
43
0
Order By: Relevance
“…Although Mahidol and wild type variants do not differ in terms of K m for NADP + or glucose-6-phosphate and have similar catalytic efficiency, the thermo-stability of Mahidol variant is less than that of wild type G6PD enzyme and the folding properties of Mahidol protein are also impaired [21]. It has been reported that c.G487A substitution could reduce enzyme activity to 5–32% of wild-type activity which is consistent with our study results [28, 30]. G6PD Mahidol variant creates an Alu I restriction site (AGCT) which can be used to differentiate between wild type and G6PD Mahidol variant using PCR-RFLP method [31].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although Mahidol and wild type variants do not differ in terms of K m for NADP + or glucose-6-phosphate and have similar catalytic efficiency, the thermo-stability of Mahidol variant is less than that of wild type G6PD enzyme and the folding properties of Mahidol protein are also impaired [21]. It has been reported that c.G487A substitution could reduce enzyme activity to 5–32% of wild-type activity which is consistent with our study results [28, 30]. G6PD Mahidol variant creates an Alu I restriction site (AGCT) which can be used to differentiate between wild type and G6PD Mahidol variant using PCR-RFLP method [31].…”
Section: Discussionsupporting
confidence: 91%
“…G6PD Mahidol is the most common deficient variant (occurs in 88–96% of G6PD-deficient subjects) in Thai-Myanmar border area [2628]. This variant provides selective advantage against Plasmodium vivax but not against Plasmodium falciparum , which stipulates Plasmodium vivax has been the driving force for selective advantage conferred by Mahidol variant [29].…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that the key pathogenic mutations of G6PD among the Dai and Jingpo groups of the Dehong prefecture were rs137852314 G>A, rs72554664 G>A, rs72554665 G>T, and rs137852341 G>T. The rs137852314 G>A and rs137852341 G>T mutations are frequently found across Southeast Asia, especially among the population of Myanmar [21] . Since the Dehong prefecture shares a border with Myanmar, frequent social exchanges between the local populations result in a genetic exchange.…”
Section: Discussionmentioning
confidence: 69%
“…There were a total of 16 ethnic populations included in the current study, and the minorities were mainly distributed in the provinces of Hainan, Guangxi, and Zhejiang. Considering that the variant frequency is related to ethnic factors (Cai, Filosa, & Martini, ; Hu et al, ; Li et al, ; Yang et al, ), we analyzed the ethnic information of the 10,357 newborns. The G6PD pathogenic variants were then evaluated according to each ethnic group (Table ).…”
Section: Resultsmentioning
confidence: 99%